Efficacy and tolerability studies evaluating a sleep aid and analgesic combination of naproxen sodium and diphenhydramine in the dental impaction pain model in subjects with induced transient insomnia. Issue 10 (21st May 2015) - Cooper, S.; Laurora, I.; Wang, Y.; Venkataraman, P.; An, R.; Roth, T.
Summary Study Objectives The aim of this study was to evaluate the efficacy and tolerability of novel combination naproxen sodium (NS) and diphenhydramine (DPH) in subjects with postoperative dental pain along with transient insomnia induced by 5 h sleep phase advance. The present studies aimed to demonstrate the added benefit and optimal dosages of the combination product over individual ingredients alone in improving sleep and pain. Methods Each of the two studies was a two‐centre, randomised, double‐blind and double‐dummy trial. In the first study, subjects were randomised into one of the following treatment arms: NS 440 mg/DPH 50 mg, NS 220 mg/DPH 50 mg, NS 440 mg or DPH 50 mg. In the second study, subjects received either NS 440 mg/DPH 25 mg, NS 440 mg or DPH 50 mg. The co‐primary end‐points in both studies were wake time after sleep onset (WASO) and sleep latency (SL) measured by actigraphy. Other secondary sleep and pain end‐points were also assessed. Results The intent‐to‐treat population included 712 and 267 subjects from studies one and two, respectively. In the first study, only the NS 440 mg/DPH 50 mg combination showed significant improvements in both WASO vs. NS alone (−70.3 min p = 0.0002) and SL vs. DPH alone (25.50 and 41.50 min respectively, p < 0.0001). In the second study, the NS 440 mg/DPH 25 mg combination failed to show any significant improvements vs. either component alone. Conclusions Only the NS 440 mg/DPH 50 mg combination demonstrated improvement in both sleep latency vs. DPH 50 mg and sleep maintenance (WASO) vs. NS 440 mg. There were no serious or unexpected adverse events reported in either study. Clinical Trial Registration: NCT01280591 (study 1); NCT01495858 (study 2)